2020
DOI: 10.1186/s13089-020-0153-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of point-of-care ultrasound in the diagnosis and management of necrotizing soft tissue infections

Abstract: Background: Necrotizing soft tissue infections are associated with high morbidity and mortality, even when the correct treatment is initiated. The diagnosis of these conditions is hard and the most sensitive methods are time-consuming, expensive and not readily available. Point-of-care ultrasound can complement clinical evaluation to increase the diagnostic accuracy. Case presentation: We bring a case of a woman, without comorbidities, who presented to the emergency department with signs of soft tissue infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…In addition, it provides information to help distinguish between simple and necrotizing soft tissue infections 1 , but in early stages of presentation it may not show obvious changes. Findings congruent with type II NF are the thickening of the subcutaneous tissue and the appearance of hypoechogenic areas corresponding to fluid accumulation along the deep fascia 1,19,20 . Increased echogenicity of fat may and the doctor's are more important than the total score obtained.…”
Section: Imaging Studiesmentioning
confidence: 98%
“…In addition, it provides information to help distinguish between simple and necrotizing soft tissue infections 1 , but in early stages of presentation it may not show obvious changes. Findings congruent with type II NF are the thickening of the subcutaneous tissue and the appearance of hypoechogenic areas corresponding to fluid accumulation along the deep fascia 1,19,20 . Increased echogenicity of fat may and the doctor's are more important than the total score obtained.…”
Section: Imaging Studiesmentioning
confidence: 98%
“…US has the advantage of being rapidly performed at the bedside and may help differentiate simple cellulitis from NSTIs [ 45 ], but again is not considered highly accurate nor definitive in most settings. Point-of-care US (POCUS) can improve diagnose accuracy for NSTI when used in combination with clinical evaluation as it is increasingly available, fast and can be performed at the bedside [ 59 ]. The main ultrasound findings are summarized in loss of the normal tissue architecture to a “cobblestone” appearance, with irregularity and thickening of the fascia, abnormal fluid collections along the fascia, seen as hypoechogenic zones, and, in more advanced cases, the presence subcutaneous air, defined by hyperechogenic foci with a posterior dirty acoustic shadowing.…”
Section: Necrotizing Infectionsmentioning
confidence: 99%
“…The treatment principles of chronic wounds mainly include improving the body’s overall state, improving the blood supply to the wound, reducing the inflammatory response, promoting the epithelialization of wound skin, and promoting granulation tissue growth through pharmacological or nonpharmacological therapies [ 8 , 9 ]. At present, studies have reported some therapies for the treatment of chronic wounds, such as ultrasound debridement [ 10 ], biological debridement [ 11 ], silver dressing [ 12 ], negative-pressure wound therapy [ 13 ], platelet-rich plasma [ 14 ], and growth factor therapy [ 15 ]. Due to the lack of clinical evidence, these wound treatment methods currently fail to show obvious advantages.…”
Section: Introductionmentioning
confidence: 99%